Ocena zagrożenia ekosystemów leśnych przez transport kołowy na przykładzie drogi krajowej nr 2 w nadleśnictwie Rzepin = Risk assesment for the forest areas caused by road transportation on the example of road no. 2 in Rzepin forestry - Pilc, Lesław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The observation of pine growth occurence of arboreal lichens and localization of pest gradation demonstrate that traffic emission in a selected part of highway No.2 pose threat to adjacent forest ecosystems. The level of this threat is magnified by fires which are caused, to some degree, by traffic participants.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); zanieczyszczenia komunikacyjne; ekosystemy leśne; traffic air pollution; forest ecosystems